Experts’ validation on competence index for teaching librarians in academic libraries in higher education: Content validity index (CVI) approach - Abu, Roziya; Dzulkipli, Mohd Razif; Shaifuddin, Norshila (e-International Publishing House, Ltd., UK., 2025)
This study uses the CVI approach to evaluate the content validity of a competence index designed for teaching librarians in academic libraries, employing the CVI approach. A purposive sampling method was used to select eight experts from eight public universities, eachwith over 20 years of experience as academic librarians, to assess the index. The evaluation comprised 108items across three main constructs. Results indicated, three items scored below the minimum I-CVI score, while 86items achieved a perfect score of 1.0. The S-CVI yielded an average score of 0.97and a universal agreement score of 0.80, confirming the overall validity of the competence index.